ANALISIS EFEKTIVITAS DAN EFISIENSI PEMUNGUTAN RETRIBUSI PASAR DI KABUPATEN SUMBAWA - S Suprianto; Indah Mayasari (Jurnal Ekonomi & Bisnis, 2022)
This study aims to analyze the effectiveness and efficiency of collecting market retribution in Sumbawa Regency. This research is a descriptive research that aims to study descriptively the effectiveness and efficiency of collecting market retribution in Sumbawa Regency in 2015-2021. The type of data used is quantitative data in the form of revenue target data, revenue realization, and market retribution collection costs in Sumbawa Regency for 2015-2021 obtained from documents and archives available at the Sumbawa Regency Revenue and Financial Management Service. To measure the performance of local governments in mobilizing PAD revenues originating from market levies, it is carried out by using the effectiveness and efficiency ratios of market retribution receipts. Based on the results of the research that has been done, it can be concluded that the ratio of the effectiveness of collecting market retribution for Sumbawa Regency in 2015-2021 is in the very effective category. This level of performance effectiveness shows the success of the local government in achieving the goals that have been set. Meanwhile, the efficiency ratio for collecting market levies for Sumbawa Regency in 2015-2021 is in the fairly efficient category. The local government of Sumbawa Regency spends relatively low costs to realize the revenue target it receives so that it can be said that the performance of the local government in mobilizing PAD revenues originating from market retribution collection is quite efficient.